Pengembangan Ekowisata Berkelanjutan Taman Rusa Sekupang Berbasis Media Tiktok - Rafa Khoirunnisa; Oda I.B. Hariyanto; Ratih Anggraini (Universitas Multi Data Palembang, 2026)
This study aims to analyze the development of sustainable ecotourism in Sekupang Deer Park based on TikTok media, with a focus on promotional strategies, visual content quality, and consistency of educational messages on conservation. The study uses a qualitative approach with a case study method. Data were obtained through in-depth interviews with managers and TikTok administrators, field observations, and digital content analysis, then analyzed descriptively using Miles and Huberman's interactive model. The results show that TikTok has been used as a promotional medium, but it has not been optimized and managed strategically. The visual content is attractive, but it emphasizes entertainment and visit promotion rather than educational messages about conservation. Messages about environmental preservation, deer conservation, and sustainable ecotourism principles are inconsistent, so that a strong sustainable ecotourism identity has not yet been established. A planned and integrated content strategy between promotion, education, and sustainability needs to be implemented in order to achieve ecotourism goals.